Design, tropicalization and manufacturing of telecommunications equipment in the Latin American and Caribbean countries - Santoyo, Arturo Serrano (UNIDO ViennaAT, 1993)
Examines the telecommunications sector scenario in Latin America and the Caribbean, and looks at local manufacturing of telecommunications equipment there. Proposes a scheme to stimulate local manufacturing of telecommunications equipment in Latin America and the Caribbean.